Selectivity of potentiometric sensors integrated with paper-based solution sampling for determination of heavy metals in environmental samples containing high solid to liquid ratios - Yip, Jane Si Qi (Nanyang Technological University, 2022)
Paper-based potentiometry is a promising technique for determination of heavy metal in samples containing high solid to liquid ratios. There have been various parameters used to determine the performance of Pb2+-ISEs coupled with paper-based potentiometry, such as potentiometric working range and slope. As selectivity is an important parameter characterizing ISEs that presents the ability of the electrode to detect the target primary ion in the presence of other interfering ions. Pb2+-ISEs were used to investigate the different responses of metal ion sample solutions on paper-based sampling. However, there are some challenges in the determination of heavy metals in samples which are connected to the inherent interactions between paper substates and the analyte causing a super-Nernstian response of the heavy metal sensitive ISEs.